2018
DOI: 10.22159/ijpps.2018v10i1.21665
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic, Physicochemical and Phytochemical Analysis of Gardenia Jasminoides (Ellis)

Abstract: ABSTARCTObjective: To evaluate the microscopical, physicochemical and phytochemical analysis of Gardenia jasminoides (Ellis). Methods:The leaves of Gardenia jasminoides (Ellis) was studied through macroscopic, microscopic, physicochemical standards such as moisture content, ash values, extractive values and phytochemical analysis includes preliminary screening and quantification of important secondary metabolites were carried out as per the standard procedures are given in Indian Ayurvedic Pharmacopeia.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
(5 reference statements)
2
5
0
3
Order By: Relevance
“…The ash content was, however, higher in the leaves, followed by fruit and flower tissues (~7%). The value falls within the reference range of ash content in Gardenia fruit ( 30 ). Phytopigments are mainly classified into fat-soluble pigments, which are mainly present in the plastid of the plant protoplasm, and water-soluble pigments, which dissolve in the cell sap ( 6 ).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The ash content was, however, higher in the leaves, followed by fruit and flower tissues (~7%). The value falls within the reference range of ash content in Gardenia fruit ( 30 ). Phytopigments are mainly classified into fat-soluble pigments, which are mainly present in the plastid of the plant protoplasm, and water-soluble pigments, which dissolve in the cell sap ( 6 ).…”
Section: Resultssupporting
confidence: 70%
“…Among the solvent combinations tested, methanol gave the highest yield followed by DIH 2 O, ethyl acetate, and dichloromethane. Kesavan et al ( 30 ) reported a low yield of Gardenia extracts when low polar organic solvents (namely, ethyl acetate and dichloromethane) were used. The yellow pigment appeared in high polar organic solvents (methanol, DIH 2 O, and ethyl acetate), mainly from the fruit and floral tissues of Gardenia .…”
Section: Resultsmentioning
confidence: 99%
“…Calcium oxalate crystals are abundant in the mesophyll tissue of the leaf. Similar results were obtained in the P. grandiflora, Portulaca [18,20]. The crystals are druses, which are spherical bodies with spiny surface.…”
Section: Crystal Distributionsupporting
confidence: 81%
“…It has been reported that G . jasminoides leaves possess alkaloid, flavonoid, saponin, tannin, and phenolic compounds 11 . Therefore, extracts from the leaves of G .…”
Section: Introductionmentioning
confidence: 99%